The angiogenesis. - Sprindzuk, M. V. (Морфологія / Morphologia / Morfologìâ, 2010)
The research theme of angiogenesis: the development of blood vessels from preexisting ones is one of the most financially supported medical scientific topics in the world. It is connected with the fact, that 500 000 000 people require the therapeutic correction of the pathological processes of angiogenesis. In the review article only the brightest research articles knowingly predominantly Russian are systematized. The paper is well illustrated, to provide the understandable educational resource. The biochemical and pathophysiological questions of angiogenesis are discussed in close relation to the modern angiogenic pharmacotherapy. The purpose of the article is to present to the reader an opportunity to discover the biomedical research challenge of the 21 century: the pathological blood supply, vascularization and the associated phenomena.